Tradisi Bahts Al-Masail Nahdhatul Ulama (NU): Pematangan Pemikiran Fikih Adil Gender Husein Muhammad - Eni Zulaiha; B Busro (Sunan Kalijaga State Islamic University & The Asia Foundation, 2020)
Artikel ini bertujuan mengungkapkan irisan penting tradisi Bahtstal-Masail NU dalam pemikiran fikih adil gender oleh Husein Muhammad. Paper ini menemukan 3 poin besar dalam (1) dinamika metodologi istinbath hukum dalam tradisi Bahtstal-Masail NU memiliki tantangan zaman modern; (2) Bahtstal-Masail NU dengan metode taqlidul manhaji dan Bahsul Masail Diniyyah mauduiyyah memiliki metode baru dalam langkah akademis; (3) pengaruh pemikiran Husein Muhamad berlatarbelakang dari pola asuh dalam keluarga Kyai NU, pendidikan pesantren, aktivitas Politik serta Masyarakat, pengalaman kajian- P3M, dan Bahts al-Masail dari sosok Abdurahman Wahid. Paper ini membuktikan tentang tradisi Bahts al-Masail NU menjadi bagian penting dalam pemikiran fikih adil gender Husein Muhammad terutama setelah Munas Lampung tahun 1992.[The article aims to reveal an essential part of the NU’s Bahtstal-Masail lesson in fiqh gender by Husein Muhammad. The paper finds three significant points in (1) the issue of the istinbath methodology in the bahstal-Masail process in NU tradition, in which has modern challenges; (2) the taqlidul manhaji method and Bahsul Masail Diniyyah mauduiyyah in NU Bahtstal-Masail have a new method in academic steps; (3) the thoughts Husein Muhamad’s idea takes from the background of parenting in the NU Kyai family, Islamic boarding school education, Political and Community activities, P3M-study experience, and Bahts al-Masail from the figure of Abdurahman Wahid. The paper proves that the NU Bahts al-Masail lesson tradition is an essential part of Husein Muhammad’s gender Issue for knowledge of fiqh for equal humanity. The idea was necessary when the meeting did in munas Lampung in 1992.]